DIAGNOSIS SEPSIS MENGGUNAKAN PROCALCITONIN - Buchori Buchori; Prihatini Prihatini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Sepsis can be difficult to distinguish from non-infections conditions in critically ill patients with clinical signs of inflammation.Diagnosis of sepsis by conventional methods (erythrocyte sedimentation rate, CRP) are difficult to be confirmed. Procalcitonin (PCT)was found in 1990s, which number was enhanced in bacterial and fungi infections. Procalcitonin (PCT) is calcitonin (PCT) prohormonwhich presence increasing in sepsis and severe diseases. Procalcitonin (PCT) can be measured in serum and plasma by immunolometricmethods (immunoassay). The process needs 30 minutes to 1.5 hours depends on the selected method. It can be hope in the future,that methods of Procalcitonin (PCT) measurement can used as a means for early sepsis detection and can distinguish between systemicinfection and acute inflammatory disease.